Child labour and international trade : an economic perspective - Hemmer, Hans-Rimbert; Steger, Thomas; Wilhelm, Rainer; Justus Liebig University Giessen (My University, 1997)
Child labour is a widespread phenomenon. Although economic activities of children have been commonplace even before the industrialisation, it has in the meanwhile become a lasting symbol of the industrial revolution and of industrialisation in general. In most countries the inclusion of children in the labour force is legally restricted. Nevertheless, economic activities of children, most of these within their families, continue to be an everyday feature of economic development, especially in the poorer countries. Beside cultural or social factors, these economic activities are mainly determined by economic forces. Hence, economic conditions most likely play a fundamental role in explaining child labour. Economic development trends which change the economic conditions therefore influence the extent of child labour.
Keywords: ddc:330